Pitch learning and the implications for music education - Byrd, Audrey S (Rhodes University, Faculty of Humanities, Department of Music, 1977)
A study of pitch learning must outline first the procedures involved in such learning and then identify specific factors appearing to influence the learning of pitch. Once identified, each factor can then be evaluated by controlled experiment before confirming its influence. Since it is what is heard and perceived that is learnt, I have started with the process of Hearing and Perceiving, for as Arnold Abramovitz, Senior Lecturer in Psychology at Cape Town says, "the reception, processing and interpretation of acoustic symbols constitutes some of the most elusive and complex phenomena to attempt to examine, gauge and measure, due partly to the transient, ephemeral nature of sound itself."
Keywords: Musical pitch -- Instruction and study